Product Innovation As A Mediation Variable Influences Market Orientation And Entrepreneurial Orientation In Increasing The Competitive Advantage Of The Msme Sector Processed By Patin Fish In Patin Village, Koto Mesjid Village, District Xiii Koto Kampa - Fadli, Mashur; Heriyanto, Meyzi; Kasmirudin, Kasmirudin; Othman, Lie (International Journal of Science, Technology & Management, 2022)
This study aims to measure the effect of market orientation, entrepreneurial orientation, and product innovation as mediating variables on strategies to increase competitive advantage in the Catfish Processed MSME Sector in Patin Village, Koto Mesjid Village, District XIII Koto Kampar. The study used a quantitative approach where primary data was collected through a survey of 70 respondents, and the statistical technique Partial Least Square (PLS) was used to process the data. The study's results confirm that market orientation significantly affects product innovation and competitive advantage, both direct and indirect effects, through the mediation of product innovation variables. Furthermore, the entrepreneurial orientation variable influences the product innovation variable and competitive advantage, either directly or indirectly, through the product innovation variable. Still, some other factors or variables affect the competitive advantage variable.